PENGGUNAAN ANPERTE DALAM MENINGKATKAN KOMPETENSI GURU ANAK BERKEBUTUHAN KHUSUS - Pastari, Marta; Endriyani, Sri; Martini, Sri (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Applied Behavior Analysis (ABA) method is a therapy specifically designed for children with autism. The basis of the ABA method itself uses behavioral theory, namely emphasizing obedience, children's skills in imitation and establishing eye contact. For this reason, it is very important to provide Applied Behavior Analysis (ABA) training in order to increase the competence of teachers of children with special needs so that they can provide various types of therapy, especially to autistic children at the Talang Kelapa Autistic Special School in Palembang. The activity method begins with the service team identifying the teacher's initial abilities in providing therapy for autistic children through a pretest; It was found that all teachers (18 people) did not have a special education background and did not understand the correct ABA method (100%). Then training is given (demonstration and re-demonstration), after completion, another posttest is given. The results of the activity showed that 12 out of 18 people (67%) of the Talang Kelapa Palembang Autistic SLB teachers showed an increase in understanding of implementing the ABA method (score ≥ 80). It can be concluded that this training has proven useful in developing teachers' professional competence in the field of special education, especially in handling autistic children who experience behavioral disorders